2015
DOI: 10.1039/c4nj01873g
|View full text |Cite
|
Sign up to set email alerts
|

NMR, DFT and luminescence studies of the complexation of V(v) oxoions in solution with 8-hydroxyquinoline-5-sulfonate

Abstract: The complexation of vanadium(v) with 8-HQS is accompanied by marked changes in the multinuclear NMR and UV/visible absorption spectra of 8-HQS, but does not lead to a significant increase in fluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…This is suggested to be due to the presence of low-lying ligand-to-metal chargetransfer state(s). 80 However, the weakness of the emission with Crq 3 is attributed to it involving a metal based transition. Further studies are in progress to fully characterize this at room temperature and low temperature.…”
Section: Uv/visible Absorption and Luminescence Spectral Studiesmentioning
confidence: 99%
“…This is suggested to be due to the presence of low-lying ligand-to-metal chargetransfer state(s). 80 However, the weakness of the emission with Crq 3 is attributed to it involving a metal based transition. Further studies are in progress to fully characterize this at room temperature and low temperature.…”
Section: Uv/visible Absorption and Luminescence Spectral Studiesmentioning
confidence: 99%
“…Though the five-membered chelate rings formed between the NO donors and Cr(III) metal centers have increased the π-π* conjugation and conformational coplanarity of 8-hydroxyquinolinate, it is hard to detect the fluorescent signal of the two metallocomplexes. In contrast to other complexes of 8-hydroxyquinoline and its derivatives with metal ions (e.g., Al(III), Ga(III), Zn(II), or Cd(II)), the 3 d 3 Cr(III) ion exhibits striking quenching effect, which might be attributed to the lowest energy transition being metal rather than ligand based [ 34 , 39 ]. The striking fluorescence response of the two 8-hydroxyquinolinate based ligand towards Cr 3+ both in solid and solution indicated they could serve as a good heavy metal chelating agent for Cr 3+ in a range of environmental monitoring and biomedical applications.…”
Section: Resultsmentioning
confidence: 99%
“…With aromatic ligands, inductive effects at specific positions in the aromatic rings allow the identification of changes in the electronic environment together with insights into the nature of the metal-ligand bonds on complexation, and the structure of the chelate species, in particular the symmetry of the coordinated ligands, 57 as illustrated in our studies of the complexation of 8-HQS with Zn 2+ , Cd 2+ , Hg 2+ , Al 3+ , Ga 3+ and V(V). [35][36][37][38][39] The combination of proton, carbon-13 and metal ion NMR can provide valuable structural information, including the type of metal centre present in these complexes, and also metal oxoions of vanadate, molybdate and tungstate with relevant ligands. [37][38][39]43,44,[58][59][60][61][62][63][64][65][66][67] In previous studies we have characterized a large number of species, and have found that the 183 W and 95 Mo NMR chemical shift ranges of homologous complexes of W(VI) and Mo(VI) show a linear correlation (δ W = 1.8δ Mo − 137.3), which parallels Scheme 1 the ratio of nuclear charges.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38][39] The combination of proton, carbon-13 and metal ion NMR can provide valuable structural information, including the type of metal centre present in these complexes, and also metal oxoions of vanadate, molybdate and tungstate with relevant ligands. [37][38][39]43,44,[58][59][60][61][62][63][64][65][66][67] In previous studies we have characterized a large number of species, and have found that the 183 W and 95 Mo NMR chemical shift ranges of homologous complexes of W(VI) and Mo(VI) show a linear correlation (δ W = 1.8δ Mo − 137.3), which parallels Scheme 1 the ratio of nuclear charges. 65,67 This relationship has proved to be useful in comparative studies in the identification and structural characterisation of homologous species of Mo(VI) and W(VI).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation